The Factors That Modify the Rate of Damage and Decomposition of Nuphar lutea Leaves: An Example from a Shallow Eutrophic Lake - Ścibior, Radosław; Stryjecki, Robert; Różańska-Boczula, Monika; Demetraki-Paleolog, Andrzej; Kowalczyk-Pecka, Danuta; Strachecka, Aneta (Polish Journal of Natural Sciences, 2023)
The rate and degree of damage to the leaves of yellow water lily Nuphar lutea in the shallow eutrophic lake was studied. Three factors were analysed: gnawing by Galerucella nymphaeae, the activity of microorganisms, and physical damage. Differences in the abundance, density and biomass of larvae and adult forms of G. nymphaeae were found between the two study sites. Site I was more favourable to the development of leaf beetles. The larger G. nymphaeae populations at site I resulted in greater leaf damage by this beetle. In turn, greater leaf damage due to feeding by G. nymphaeae resulted in greater damage resulting from microbial activity. The most likely reason for the smaller degree of damage to leaves at site II were their greater exposure to wind and waves. These two environmental factors impeded the development of the G. nymphaeae population and thus resulted in less damage to N. lutea leaves and a slower rate of decomposition.